Parenchymal involvement on CT pulmonary angiography in SARS-CoV-2 Alpha variant infection and correlation of COVID-19 CT severity score with clinical disease severity and short-term prognosis in a UK cohort. Issue 2 (February 2022) - Tsakok, M.T.; Watson, R.A.; Lumley, S.F.; Khan, F.; Qamhawi, Z.; Lodge, A.; Xie, C.; Shine, B.; Matthews, P.; Jeffery, K.; Eyre, D.W.; Benamore, R.; et al.
Abstract : AIM: To determine if there is a difference in radiological, biochemical, or clinical severity between patients infected with Alpha-variant SARS-CoV-2 compared with those infected with pre-existing strains, and to determine if the computed tomography (CT) severity score (CTSS) for COVID-19 pneumonitis correlates with clinical severity and can prognosticate outcomes. MATERIALS AND METHODS: Blinded CTSS scoring was applied to 137 hospital patients who had undergone both CT pulmonary angiography (CTPA) and whole-genome sequencing of SARS-CoV-2 within 14 days of CTPA between 1/12/20–5/1/21. RESULTS: There was no evidence of a difference in imaging severity on CTPA, viral load, clinical parameters of severity, or outcomes between Alpha and preceding variants. CTSS on CTPA strongly correlates with clinical and biochemical severity at the time of CTPA, and with patient outcomes. Classifying CTSS into a binary value of "high" and "low", with a cut-off score of 14, patients with a high score have a significantly increased risk of deterioration, as defined by subsequent admission to critical care or death (multivariate hazard ratio [HR] 2.76, p< 0.001), and hospital length of stay (17.4 versus 7.9 days, p< 0.0001). CONCLUSION: There was no evidence of a difference in radiological severity of Alpha variant infection compared with pre-existing strains. High CTSS applied to CTPA is associated with increased risk of COVID-19 severity and poorer clinical outcomes and may be of use particularly in settings where CT is not performed for diagnosis of COVID-19 but rather is used following clinical deterioration. Highlights: CT severity score (CTSS) correlates with clinical and biochemical severity and patient outcomes. CTSS ≥14 associated with near x3 risk of critical care admission/death and x2 length hospital stay. No evidence of CTSS difference between alpha and pre-existing COVID-19 variant infections. No evidence of difference in outcomes between alpha and pre-existing COVID-19 variants infections.